Effect of fluorine ingestion on rumen metabolites and protozoal population - KAPOOR, V; PRASAD, T; PALIWAL, V K (The Indian Journal of Animal Sciences, 2014)
Rumen flstulated calves (4) aged 1.5 years, were given 4 different dietary treatments in a 4 x 4 latin- square switchover design study. The diet of all animals consisted of maize fodder and concentrate mixture (70: 30). The mineral mixture (included in the concentrate mixture) of groups 1 and 2 contained dicalcium phosphate (DCP) and in groups 3and 4 it was substituted (w/w) with rock phosphate (RP). In addition. sodium fluoride (NaF) was added in groups 2 and4 to achieve 80 ppm additional F. The dietary F levels in the 4 groups were 7, 80, 86 and 159 ppm respectively. Additionof NaF either to DCP or to RP significantly increased ruminal F and decreased total VFA concentration. The molar proportion of acetate and propionate remained unaffected but slight increase in molar proportion of butyrate was noticed at higher F intake. There was significant increase in total -N and TCA-precipitable -N at higher F intake. The protozoalpopulation increased at highest level of F intake (159 ppm F group 4) but individual protozoal population remainedunaffected due to various dietary F levels.